Kandungan Nutrisi dan Aktivitas Antimikroba Ekstrak Beras Merah - Dina Fitriyah; Dessya Putri Ayu; Surya Dewi Puspita; Ria Chandra Kartika; Mohammad Ubaidillah (Universitas Muhammadiyah Semarang, 2022)
Red rice is an important commodity with antioxidant activity. The antioxidant content in red rice can help to overcome various health problems. Red rice extract has the potential to be a functional drink that is rich in nutrients and antioxidants. In Indonesia, studies regarding the nutritional content and antimicrobial activity of red rice extract are still few and poorly explored. This study aims to determine nutritional content and potency of antimicrobial red rice extract. Four types of commercial red rice were extracted using a treatment of 90°C of temperature, 15 minutes, with the ratio of water: rice 1: 20 ml/g. The conventional extraction method using methanol was used as a comparison. The extract was measured for protein content, iron, and antimicrobial activity. Red rice extract's total protein and iron content were 0.3305-0.5660% and 0.0090-0.0141%, respectively. Red rice extract concentrated up to 100 µl can inhibit Staphylococcus aureus and Escherichia coli growth with the largest inhibition zone of 3 mm and an antimicrobial index of 0.5. The protein content of red rice extracted with our method showed a higher value when compared to conventional extraction using methanol. The presence of protein, iron, and antimicrobial activity in red rice extract can be potential as a functional drink that is good for health because the presence of iron in red rice extract has the potential to overcome iron deficiency. Moreover, the antimicrobial activity in red rice can be beneficial to inhibit the growth of bacteria that cause foodborne diseases such as S. aureus and E. coli.